ANALISIS KESULITAN MEMBACA SISWA DI SD NEGERI 023 SAMARINDA UTARA TAHUN PEMBELAJARAN 2018/2019 - Agus Salim, Nur; Oktaviani, Siska; Winarti, Jeni (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This research was a qualitative study. It based on the finding of several students who have difficulty in reading that causes students to not be able to participate in learning well and cannot complete assignments. The technique used in this study was triangulation of sources for one data by comparing the results of interviews with existing data in documents and observations. The results showed students who have difficulty reading from classes I, II and III, there are 6 students who have difficulty reading. Factors that influence reading difficulties are psychological factors and environmental factors. The results showed some location of students' reading difficulties, when reading often shows sentences, reads word for word, often looks at pictures in books. The factors that cause students to have difficulty reading, including, lack of students' willingness to learn to read, lack of attention from parents, young people forget the delivery of teachers.